Similarities and Differences of Global Dust Storms in MY 25, 28, and 34. Issue 3 (10th March 2020) - Wolkenberg, P.; Giuranna, M.; Smith, M. D.; Grassi, D.; Amoroso, M.
Abstract: To better understand the dust cycle on Mars during years with planet‐encircling dust storms, we analyze the last three events that took place in Mars Year (MY) 25, MY 28, and MY 34. Global dust storms that occurred in MY 25 and MY 34 (June 2018) were taking place during equinox, while the MY 28 storm had an onset after perihelion. Before the expansion phase of the MY 25 and MY 34 storms, we find similar regions (northern rim of Hellas, Arabia Terra, and Utopia Planitia) where dust is present. Possible precursor dust storms over Hellas and the southern polar cap edges were observed during MY 28 as a component of background dust activity. These features are not found in equinoctial dust storms on this scale. Dust during the MY 25 and MY 34 storms encircled the entire planet by the similar season (Ls = 193°). The MY 34 storm is characterized by a shorter decay phase compared to the events in MY 25 and MY 28. Dust opacity is correlated with atmospheric temperatures at 0.5 mbar and nighttime surface temperatures, while daytime surface temperatures are anticorrelated with dust opacity. Plain Language Summary: On Mars, one of the most variable atmospheric components is dust. We study it to better understand the cycle of its presence and absence in the Martian atmosphere. One of the particular phenomena of this cycle is the global dust storm that enshrouds the entire planet. Using data measured by two spectrometers, Thermal Infrared Emission Spectrometer onboard the Mars Global Surveyor and Planetary Fourier Spectrometer onboard the Mars Express orbiters, we investigate similarities and differences of the three most recent global dust storms that have occurred on Mars. We find similarities between the two global dust storms that took place in 2001 and 2018 (Mars Year [MY] 25 and 34). They encircled the entire planet in the equinox season. The storms in MY 25 and MY 28 dissipated over a very long timescale compared to the global dust storm of MY 34. Local dust storms in the northern rim of Hellas, Arabia Terra, and Utopia Planitia were observed before the onset of MY 25 and MY 34 global events. Key Points: The three global dust storms considered here have a similar duration of expansion phase Global dust storm in Mars Year (MY) 34 is characterized by a shorter decay phase in comparison with the decay phases in MY 28 and MY 25 storms Relatively large dust opacities are observed over Hellas and southern polar edge regions long before the onset of MY 28 storm